2009
DOI: 10.1111/j.1467-971x.2009.01599.x
|View full text |Cite
|
Sign up to set email alerts
|

English in the Jordanian Context

Abstract: The paper explores the status of English in Jordan as reflected in newspaper job advertisements (ads) published in 1985, 1995 and 2005, and English language documents in the educational domain. The study shows a steady increase in the percentage of English ads paralleled with a steady decrease in the percentage of Arabic ads. Further, it reports a significant increase in the percentage of ads that make English proficiency a precondition for employment. The study also shows a change in the jobs demanding Engli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…The emergence and dominance of the English language in today's society cannot be ignored and, as such, it has had profound effects not only on the ways in which we do business but also on the education of the next generation (Sharifian 2009). Learning English is considered to be a high priority by the government of Jordan and, as a result, is a compulsory university-level subject that students are required to pass (Hamdan and Hatab 2009).…”
mentioning
confidence: 99%
“…The emergence and dominance of the English language in today's society cannot be ignored and, as such, it has had profound effects not only on the ways in which we do business but also on the education of the next generation (Sharifian 2009). Learning English is considered to be a high priority by the government of Jordan and, as a result, is a compulsory university-level subject that students are required to pass (Hamdan and Hatab 2009).…”
mentioning
confidence: 99%
“…English is not the Local Language The use of English in the specific organizational communication genre of job ads in EFL countries has been commented on in scholarly publications relating to, for example, Finland [22], [23]; Germany [13], [24], [25]; Jordan [3]; Sweden [5]; Switzerland [6]; and Turkey [2]. Corpus analyses of the use of English in job ads in non-English-speaking countries have shown that job ads can be completely or partly in English.…”
Section: Use Of English In Job Ads In Countries Wherementioning
confidence: 99%
“…For instance, an analysis of 419 advertisements from two Turkish daily newspapers by Dogancay-Aktuna [2] revealed that 22% were completely in English. Hamdan and Hatab [3] analyzed a corpus of nearly 3000 job ads from two Jordanian daily Arabic newspapers, published in 1985, 1995, and 2005. They found that the use of completely English job ads in these newspapers increased from 4% (1985) to 23% (1995) and to 29% (2005).…”
Section: Use Of English In Job Ads In Countries Wherementioning
confidence: 99%
“…The scientific works declare that the proper percentage amount of the working fluid in loop thermosyphon is in the range of 40 -60% of the total loop thermosyphon volume [10,11,12]. In this work was performed experiment to finding proper amount of the working fluid for the LT with working fluid percentage amount in the range of 20 -70 %.…”
Section: :Runlqj Ioxlg Dprxqw Rswlrqmentioning
confidence: 99%